Fostering Undergraduate Students’ Reading Performance in English Discourse through Problem-Based Learning Model - Alek Alek (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
Choosing and applying appropriate models or strategies in teaching and learning reading comprehension may lead to enhance the quality of both teacher and students’ performance or achievement. Fostering students’ reading performance is the primary endeavor to master other English skills. This investigation has done in five main stages which cover pre-test, planning, acting, observing, reflecting, and evaluation of the results. This recent study expects to reveal and describe the application of Problem-Based Learning (PBL) in fostering the students’ reading English discourses. The instruments used in gathering the data were the observation sheets, questionnaire, and tests. There were 32 participants chosen to form the fourth-semester students which majoring in English education program of UIN Syarif Hidayatullah Jakarta. The data were analyzed qualitatively and quantitatively. The results show that the students’ scores since the pre-action test, first cycle up to the second cycle undergo increasing which tends to ‘positive category’ and ended with ‘good level’ (78 scores or high qualification category). It could be summarized that the application of PBL model towards EFL undergraduate students is effective in teaching and learning of English discourse reading comprehension.